Corcomroe Cistercian Monastery, west door, jamb and arch - O'Donovan, Danielle (My University, 2008)
Door jamb and arch moulding, comprising from intrados: chamfer, hollow, triplet of roll-and-fillets, hollow, quadrant, quadrant. The hood comprises a sunk chamfer.
Keywords: Architecture, Gothic -- Ireland; Corcomroe Abbey (Ireland); Architecture, Cistercian; Gothic doorways; Late Medieval; roll-and-fillet moldings; roll moldings; fillets (moldings); moldings, hollow; hood moldings